2001
DOI: 10.3171/jns.2001.94.3.0403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperbaric oxygenation therapy on cerebral metabolism and intracranial pressure in severely brain injured patients

Abstract: The increased CMRO2 and decreased CSF lactate levels after treatment indicate that HBO may improve aerobic metabolism in severely brain injured patients. This is the first study to demonstrate a prolonged effect of HBO treatment on CBF and cerebral metabolism. On the basis of their data the authors assert that shorter, more frequent exposure to HBO may optimize treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(107 citation statements)
references
References 52 publications
4
102
0
1
Order By: Relevance
“…90 Treatment of TBI patients with normobaric hyperoxia has shown variable results. Significant improvement 91,92 or no improvement 93 in cerebral metabolism, a decrease of lactate levels, 91,94 -96 a reduction of ischemic brain volume 92 and ICP 96 were observed. Hyperoxia treatment has also resulted in either no change 92 and in only some studies a decrease 90,96 of L/P ratio.…”
Section: Clinical Studies With Hyperoxiamentioning
confidence: 94%
“…90 Treatment of TBI patients with normobaric hyperoxia has shown variable results. Significant improvement 91,92 or no improvement 93 in cerebral metabolism, a decrease of lactate levels, 91,94 -96 a reduction of ischemic brain volume 92 and ICP 96 were observed. Hyperoxia treatment has also resulted in either no change 92 and in only some studies a decrease 90,96 of L/P ratio.…”
Section: Clinical Studies With Hyperoxiamentioning
confidence: 94%
“…44,45 The data suggest that HBO 2 enables the brain to use increased FiO 2 in the posttreatment period. Experimental investigations also support the concept of using HBO 2 followed by continued increased O 2 at normobaric pressures as a single treatment.…”
mentioning
confidence: 96%
“…The cerebrovascular response to hyperoxia has been investigated in physiological and pathological conditions, and it has been shown that there is a cerebral blood flow (CBF) reduction in response to hyperoxia ranging from 9% to 27% (Johnston et al 2003). In addition, Rockswold et al (2001) investigated the effects of hyperoxia therapy at 1.5 atm on CBF and metabolism. The authors observed that at 1 and 6 h post treatment, there was an increase in CBF in the group with decreased baseline values, whereas there was a decrease in CBF in the patients with increased pretreatment values.…”
Section: Discussionmentioning
confidence: 99%